Analisis Morfologi Kata Serapan Bahasa Arab Dalam Bahasa Indonesia - Afjalurrahmansyah, Afjalurrahmansyah (FAKULTAS TARBIYAH, 2021)
This study analyzes the morphology of Arabic loanwords in Indonesian, an analysis of the transformation of the morphological aspects of a word from the source language (Arabic) into the absorbent language (Indonesian). The morphological aspect is a study in the field of linguistics that studies and analyzes the structure, form, and classification of words. This problem occurs because the process of taking or absorbing Indonesian words from Arabic generally does not pay attention to the type and word of origin, and also because of differences in rules between Arabic and Indonesian which causes a number of loan words to change word categories. This research is classified as library research using a morphological linguistic approach and a historical approach. The results showed that changes in the morphological aspects of Arabic loanwords in Indonesian include changes or inflections in terms of category or word class, inflections on the quantity or number of words, and changes in the form of simplex words and complex words into simplex lexemes in Indonesian